rd-fpm - Språkbanken Text (University of Gothenburg, 2024)
Regeringens faktapromemorior om EU-kommissionens förslag
Riksdagens öppna data: Faktapromemoria
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik